Detecting and representing relevant web deltas using web join - BHOWMICK, Sourav S. (Institutional Knowledge at Singapore Management University, 2000)
In this paper, we show how to detect and represent web deltas, i.e., changes in Web information, that are relevant to a user's query in the context of our web warehousing system called WHOWEDA (Warehouse of Web Data). In WHOWEDA, Web information is materialized views stored in web tables and can be manipulated and analyzed using a set of web algebraic operators. In this paper, we present a mechanism to detect relevant web deltas using web join and outer web join. We show how to represent these changes using delta web tables.